The Role of Background Knowledge in Reading Comprehension: A Critical Review. Issue 3 (29th March 2021) - Smith, Reid; Snow, Pamela; Serry, Tanya; Hammond, Lorraine
Abstract: A critical review was conducted to determine the influence background knowledge has on the reading comprehension of primary school-aged children. We identified twenty-three studies that met our criteria and focused on the links between background knowledge and reading comprehension of children in the mid to late primary years. Review findings highlight that higher levels of background knowledge have a range of effects that are influenced by the nature of the text, the quality of the situation model required, and the presence of reader misconceptions about the text. Our findings also indicate that background knowledge impacts differentially on stronger and weaker readers. Readers with lower background knowledge appear to benefit more from text with high cohesion, while weaker readers were able to compensate somewhat for their relatively weak reading skills in the context of a high degree of background knowledge. Implications of the findings for early years classroom practice are outlined, together with suggested future research directions.